Investigating recharge rates in Table Mountain springs using oxygen and hydrogen isotopes - Halenyane, Keolebogile (Department of Geological Sciences, 2018)
This thesis investigates the monthly variation in hydrogen and oxygen isotope composition of four springs at the foot of Table Mountain, and by comparing this variation with that of local rainfall, estimates are made of their recharge rate. The oxygen, hydrogen, and EC data for Main spring, De Waal spring, Albion spring, and Newlands springs for the years 2013 to 2016 are presented. The oxygen and hydrogen isotope composition of monthly rainfall collected nearby at the University of Cape Town (UCT) over the same period are also presented. The rainfall data ranges in δD and δ¹⁸O values from -57 to +18 ‰ and -8.1 to +3.19 ‰, respectively, with most δD and δ¹⁸O values between -60 and -20‰, and -10 and +4‰. The data shows seasonal pattern, with lower δD and δ¹⁸O values in winter and higher in summer. The UCT monthly rainfall samples define a meteoric water line whose equation is δD = 6.03*δ¹⁸O + 7.07, which is similar to previous versions of the equation from the 1995 to 2008 data. The range of recorded EC values for the springs are distinct, the average EC values for each of the spring is; Albion spring 207 μS/cm, Newlands spring 128 μS/cm, Main spring 171 μS/cm and De Waal 166 μS/cm. The isotope compositions of the springs are also well grouped, with each spring plotting in a distinct field on a δD and δ¹⁸O plot. Main spring has the lowest δD and δ¹⁸O values and De Waal spring has the highest δD and δ¹⁸O values. The springs' average δD and δ¹⁸O values for the three years sampled are -7.7 and -2.74‰ (Albion), -6.48 and -2.46‰ (De Waal), -11.52 and -3.48‰ (Main) and -8.49 and -3.14‰ (Newlands). The d-excess of the rainfall range between -11.56 and +33.12 and for the springs is between 0.17 and 27.97. The summer months (low rainfall) have lower d-excess values than the winter months (higher rainfall). There is a positive relationship between the rainfall d-excess, springs d-excess and the rainfall amount, as the amount of rainfall increases the d-excess values of both the rainfall and springs increase. The change in the springs d-excess values clearly mimics that of the rainfall. The similar pattern changes of the d-excess values and δD and δ¹⁸O of the rainfall is reflected in the spring water, suggesting that recharge is occurring rather rapidly and from the d-excess values, the recovery seem to occur for some springs from month to month. De Waal spring mimics the rainfall d-excess very closely, the changes are almost at the same time, and therefore the De Waal spring is recharged the fastest, recovery occurs from month to month. Newlands d-excess does not change at the same time at the rainfall's d-excess, Newlands is the slowest spring to recover, with recharge occurring at least within three months. Main spring and Albion spring fall in between the fastest and slowest recovering spring. The springs are recharged at different rates but with the general average of recharge rate of one to three months of recovery. The difference in δD and δ¹⁸O values between the springs is best explained in terms of difference in average altitude of the potential recharge areas. Average altitude of potential recharge estimated from the topographic map is as follows: Albion spring 286 m, Newlands spring 359 m, Main Spring 518 m and for the De Waal spring 335 m. There is a strong negative correlation between δD and average altitude (r = -0.90) and for δ¹⁸O and average altitude (r = -0.82). In 2012 the annual weighted mean δ¹⁸O value of rainfall on top of Table Mountain was -4.0 ‰, therefore De Waal spring (δ¹⁸O -2.46 ‰) has a small component of mountain rainfall compared to Main spring (δ¹⁸O -3.48 ‰), with Albion spring and Newlands spring in between.